PENGARUH STRATEGI PEMBELAJARAN MIND MAPPING DAN EKSPOSITORI TERHADAP HASIL BELAJAR MATA KULIAH MENGGAMBAR TEKNIK 1 PADA PRODI PENDIDIKAN TEKNIK BANGUNAN - Ammar Azmi (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Since its inception, an active learning approach has been used. More often, it is considered active interaction during the learning process when the teacher explains the material and listens to the students. The purpose of this section of the journal is to discuss active learning, including mind mapping, particularly in vocational high schools. The goal is to provide the best overview and examples of applied learning in schools. Descriptive analysis is the method of data analysis employed, and the findings of the study demonstrated that the learning objectives of students instructed in the mind map learning strategy were It is possible to conclude from the first technical drawing course of the Building Engineering Education study program that the mind mapping learning method outperforms the expository learning strategy.